In vitro antimicrobial activity of selected herbal extracts against Mycobacterium tuberculosis - Shahab, Fatinah; Pribadhi, Adhitya Naufal (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Background: Tuberculosis (TB) is one of the deadliest infectious diseases worldwide, causing approximately two million deaths annually. Multidrug resistance presents a significant global challenge in TB treatment, necessitating prolonged medication use and extended treatment durations. There is an urgent need to discover alternative novel antimicrobial compounds. Herbal medicine offers promising prospects for drug discovery and development, warranting the screening of plant-derived compounds with favorable safety margins. Objectives: This study aimed to investigate the in vitro antimicrobial activity of extracts from five medicinal plants against Mycobacterium tuberculosis in vitro.Methods: Extracts from five herbs —Morinda citrifolia L, Nicotiana spp.L, Centella asiatica L, Allium sativum L, and Annona muricata L, —were investigated for their in vitro antimicrobial activity against M. tuberculosis using Lowenstein-Jensen medium. Antimicrobial activity was assessed by comparing bacterial colony growth on extract-containing media with that on extract-free control media. The agar dilution method was used to determine antimicrobial activity.Results: Among the tested extracts, Nicotiana spp L and Annona muricata L exhibited the strongest antimicrobial activity. These herbs contain various bioactive compounds, including alkaloids, flavonoids, and steroids, which are presumed to contribute to bacterial susceptibility. Conclusions: The findings suggest that Nicotiana spp. L. and Annona muricata L. may have therapeutic potential in TB treatment. These herbs could serve as alternative agents for combating TB and may help mitigate the adverse effects associated with standard anti-tuberculosis drugs.